Uganda: Higher Education Modernization Needed - Hyuha, Mukwanason A. (International Higher Education, 2017)
Uganda’s higher education sector has just over 200,000 students, 45 percent of whom are women. These study at 41 institutions, of which 11 are public universities. The private sector is vital and represents 72 percent of the tertiary institutions. Access by the poor is problematic. Since the 1980s, there has been tremendous growth in higher education, resulting from its ever-growing demand. Unfortunately, technical education is neglected and has been declining. Currently, mainly due to underfunding, the sector is declining in terms of quality and physical infrastructure. Hence, as a way forward, it requires overhauling, modernization, rehabilitation, and refocusing.